MOLECULAR DOCKING COMPOUNDS IN METHANOL EXTRACT OF MANGO LEAVES (Mangifera indica L.) AS ANTI-INFLAMMATORY AGENT - Vina Juliana Anggraeni; Purwaniati Purwaniati; Wempi Budiana; Thoriq Nurdin (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Previous studies have shown that mango has anti-inflammatory properties. Anti-inflammatory drugs are compounds or medicines used to treat diseases caused by inflammation. The most commonly used anti-inflammatory drug is a non-steroidal anti-inflammatory drug (NSAID). The drug works by inhibiting the enzyme cyclooxygenase (COX). The purpose of this study was to determine the profile metabolites present in the methanol extract of mango leaves and their interaction with the COX enzyme. This study includes an analysis of the compounds contained in the methanol extract of mango leaves using LCMS / MS and molecular docking studies of these compounds. Compounds detected by MS include C26H24O14, C45H84O14, Khellol-β-D-glucoside, Mangiferin, and Nevadensin-5-β-D-glucoside. Analysis of docking result was based on ΔG and Ki and the binding interactions that occur. Compounds that are compatible with COX1 and COX2 are Khellol βD glucoside with G and Ki values of 7.49 kcal/mol and 3.23 µM and 8.32 kcal/mol and 0.7919 µM, respectively. Through the molecular docking process, it was confirmed that khellol β-D-glucoside may be activated as an anti-inflammatory agent.